اإلحداد ملوظفات احلكومية أو املرأة العاملة يف وجهة نظر زعيمات عائشية يف إدارة فرع عائشية نغورو موجوكرتو - Ikhwanuddin, Mohammad; Ammar, Farikh Marzuqi; Pramana, Dekky (MAQASID, 2020)
A woman (wife) has an obligation to carry out Ihdad, because her husband has died for four months and ten days. This is a condition in which the wife must restrain or mourn. During that time, the wife should express her grief by not decorating and not leaving the house. It aims to respect the death of the husband. If the Iddah period is over, then there is no prohibition for women to decorate themselves, make proposals, and even enter into a marriage contract. But in this era, many women who have work outside to make a living such as career women or civil servants. If Ihdad is implemented, they will automatically be unable to work and will not get income. This is the main problem that will be discussed in this thesis to get a balanced answer. The author focuses the discussion on the main opinion of the elite figure of PC Aisyiah Ngoro, Mojokerto.From the background of the problem the writer formulates the problem into 3. They are 1) How is Ihdad in Islamic Sharia? 2) What is the opinion of the elite figure of PC Aisyiah Ngoro, Mojokerto about Ihdad and its application for civil servants orcareer women? 3) What is the wisdom of applying Ihdad syariah from the perspective of the elite figure of PC Aisyiah Ngoro, Mojokerto? This research is a qualitative research using interview data collection method with the object of the elite figure PCAisyiah Ngoro, Mojokerto and analyzing it using descriptive qualitative analysis of the results of the interview.The results of this study are that women (wives) who have been left by their husbands because of death are obliged to carry out Ihdad for 4 months and 10 days leaving all jewels and not leaving the house, according to the view of the elite figureof PC Aisyiah Ngoro Mojokerto a woman (wife) left by her husband may leave the house in the context of urgent and dhorurah needs, because going out to make a living for women today is part out of necessity, while still paying attention to the problem of decorating, is limited to his needs in his work, so that no man may come near him so that marriage does not occur during his Iddah. The wisdom of Ihdad is as a form of tafakkur and obedience to Allah SWT and His Rasul, maintaining the health of a woman, her temperament and honor before other men, as a form of respect for herhusband and family.